METHODS OF CALCULATION OF FOREIGN STUDENTS: THE EFFECT ON THE RUSSIAN UNIVERSITY INTERNATIONALIZATION - S. M. Yakovleva (Образование и наука)
The article is devoted to search of the solution of urgent problems of recruiting of foreign students in the Russian higher education institutions. Nowadays, in Russia the term «foreign students» is used, whereas the most part of world educational community uses the concept «international students». Distinction of concepts is connected with different methods of accounting of this category of students. Effective accounting, in turn, influences the quality of further interaction with international target audience, gives the chance of competent forming of a profile of the student and the choice of effective instruments of recruiting. Methods. The methods of comparative analysis of approaches to content of the concepts «foreign students» and «international students» are used.Results. The results of researches of the foreign and Russian authors concerning internationalization of universities and involvement of students from abroad are analysed. The concepts «foreign students» and «international students» are structured and divided. The proposals on the need of a right choice of determination for further successful recruiting according to the purposes of internationalization of higher education institutions are developed. The results of the present research have showed that further processes of involvement of students from abroad in the Russian higher educational institutions depend on the choice of a method of accounting and the corresponding terminology, arrangement of emphases on formal or substantial criteria, i. e. on indicators of internationalization or the purposes of internationalization.Scientific novelty. It is convincingly proved that new approaches to recruiting of foreign students are required in the longer term for increase of a level of internationalization of higher education institution: transition from tactical line items to strategic tasks; forming of a profile of a potential student as international, but not as a foreign subject of education.Practical significance. The materials of the investigation will be useful to the staff of departments of internationalization, international departments, departments of recruiting and academic mobility.